К вопросу о существовании NO₂, NO и O₂ - Кравченко, И. В. (НТУ "ХПИ", 2011)
The thermodynamic and kinetic calculations of the reactions of nitric oxide (IV) with water are performed. It is shown that the reaction easily proceeds arbitrarily when NO₂ is in the excited states. The NO₂ in the excited states must be in the atmosphere of Earth, especially in the daytime, since this requires the infrared radiation of the visible spectrum in the wavelength range 872–430 nm. Because of excited molecules of NO₂ dissociation at the atmosphere the molecules of nitric oxide (II) should be also present constantly. For this reason, the implementation of conversion of NO₂ to the excited states in the industrial absorption column is undesirable from the kinetic considerations.
Keywords: окисление; кислотообразование; азотная кислота; гидродинамическая кавитация; термодинамика; кинетика